Wpływ czynników antropogenicznych na powstawanie osuwisk - Kozner, Joanna (My University, 2014)
Poland landslides occur as a result of various factors. Although landslides may be generated by geological or morphological factors, they can also be caused by factors associated with human activity. Such anthropogenic factors include errors in construction, poor water management, and poor agricultural land usage. This paper aims to discuss those anthropogenic factors and assess their impact on the formation of landslides.

Osuwiska na terenie Polski powstają w wyniku działania różnych czynników inicjujących. Są to czynniki naturalne oraz związane z działalnością człowieka. Do najważniejszych czynników antropogenicznych zalicza się błędy w budownictwie, złą gospodarkę wodną, czy antropogenicznych błędy w rolniczym zagospodarowaniu terenu. Praca ta ma na celu przedstawienie czynników oraz ocenę ich wpływu na powstanie osuwiska.
Influence of anthropogenic factors on landslides
Keywords: osuwisko; czynniki antropogeniczne; błędy w budownictwie; landslide; anthropogenic factors; errors in construction